K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 8 2015

x - 2.32 : 3 = 12

=> x - 18 : 3 = 12

=> x - 6 = 12

=> x = 6 + 12 = 18        

13 tháng 11 2016

mình muốn hỏi x-18:3=12

4 tháng 12 2016

a) \(x\left(x-1\right)=0\)

\(\Rightarrow x=0\) hoặc \(x-1=0\)

+) \(x=0\)

+) \(x-1=0\Rightarrow x=1\)

Vậy \(x\in\left\{0;1\right\}\)

b) \(\left(x+2\right)\left(x-4\right)=0\)

\(\Rightarrow x+2=0\) hoặc \(x-4=0\)

+) \(x+2=0\Rightarrow x=-2\)

+) \(x-4=0\Rightarrow x=4\)

Vậy \(x\in\left\{-2;4\right\}\)

c) \(x^3.x^2=2^8:2^3\)

\(\Rightarrow x^5=2^5\)

\(\Rightarrow x=2\)

Vậy \(x=2\)

d) \(3^{x-3}-3^2=2.3^2\)

\(\Rightarrow3^{x-3}=18+9\)

\(\Rightarrow3^{x-3}=27\)

\(\Rightarrow3^{x-3}=3^3\)

\(\Rightarrow x-3=3\)

\(\Rightarrow x=6\)

Vậy \(x=6\)

4 tháng 12 2016

a) x(x-1)=0

=> x.x =0+1

=> x.x =1

=> x^2 =1

=> x^2 =1^2

=> x =1

29 tháng 8 2016

8.9 - 3.(x + 2.9) + 6=0

72 - 3x +18.3 + 6 =0

(72+18.3 +6 ) -3x =0

(72+54+6) - 3x = 0

132 - 3x = 0

132 =3x 

x = 132 :3 =44

nhớ túch đúng cho mình nha =)))

24 tháng 10 2015

(x-2)^20-(x-2)^18=0

(x-2)^18[(x-2)^2-1]=0

 suy ra (x-2)^18=0;(x-2)^2-1=0       

             x-2=0       ;(x-2)^2=1           ;(x-2)^2=-1 

              x=2          ;x-2=1                 ;x-2=-1

                               x=3                     x=1

                             

       

21 tháng 9 2015

33 . 32x - 1 = 81

33 . 32x - 1 = 34

       32x - 1 = 34 : 33 = 3

  => 2x - 1 = 1

          2x   = 2

            x   = 2 : 2 = 1 

2 tháng 1 2017

a) \(\left(\left|x\right|+3\right):5-3=12\Leftrightarrow\left|x\right|+3=45\Leftrightarrow\orbr{\begin{cases}x=42\\x=-42\end{cases}}\)

b) \(86:\left[2\left(2x-1\right)^2-7\right]+4^2=2\cdot3^2\Leftrightarrow2\left(2x-1\right)^2-7=43\Leftrightarrow\left(2x-1\right)^2=25\Leftrightarrow\orbr{\begin{cases}2x-1=-5\\2x-1=5\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-2\\x=3\end{cases}}\)

2 tháng 1 2017

a) \(\left(\left|x\right|+3\right)\div5-3=12\)

    \(\left(\left|x\right|+3\right)\div5=12+3\)

    \(\left(\left|x\right|+3\right)\div5=15\)

       \(\left|x\right|+3=15.5\)

       \(\left|x\right|+3=75\)

       \(\left|x\right|=75-3\)

       \(\left|x\right|=72\)

\(\Rightarrow\orbr{\begin{cases}x=72\\x=-72\end{cases}}\)

Vậy \(x\in\left\{72;-72\right\}\)

b) \(86\div\left[2,\left(2x-1\right)^2-7\right]+4^2=2.3^2\)

    \(86\div\left[2.\left(2x-1\right)^2-7\right]+16=18\)

    \(86\div\left[2.\left(2x-1\right)^2-7\right]=18-16\)

    \(86\div\left[2.\left(2x-1\right)^2-7\right]=2\)

                  \(2.\left(2x-1\right)^2-7=86\div2\)

                  \(2.\left(2x-1\right)^2-7=43\)

                  \(2.\left(2x-1\right)^2=43+7\)

                  \(2.\left(2x-1\right)^2=50\)

                      \(\left(2x-1\right)^2=50\div2\)

                      \(\left(2x-1\right)^2=25\)    

                      \(\left(2x-1\right)^2=5^2\)

\(\Rightarrow2x-1=5\)

                \(2x=5+1\)

                \(2x=6\)

                  \(x=6\div2\)

                  \(x=3\)